The new income tax, law and accounting - Reyes, Virgilio D. (2007)
This book discusses all the topics in the Income Tax portion for Taxation, both in the syllabus for the undergraduate Accountancy course.
Keywords: Taxation, Income--Philippines; Income Taxes--Philippines